Individual differences in goal adjustment: convergence and divergence among three theoretical models - Kappes, Cathleen; Greve, Werner (Frontiers in Psychology, 2024)
Individual differences in dealing with unattainable goals or resource-consumptive goal pursuit are conceptualized as goal adjustment processes in three theoretical approaches: accommodative coping (two-process model of developmental regulation), compensatory secondary coping (motivational theory of life-span development), and goal disengagement and goal reengagement (goal adjustment theory). The aim of this paper is to conceptually and empirically analyze convergences and divergences between the three approaches as well as their relationship with indicators of well-being and their intersections with cognitive emotion regulation. The empirical study is based on a cross-sectional online survey (N = 433; M = 28.9 years, SD = 8.4 years; 50% female). The conceptual analysis yields clear convergences, but also differences. Empirically, clear but partially nonredundant relationships between the concepts are found in structural equation models. Accommodative coping showed the strongest correlations with measures of well-being and cognitive emotion regulation. When all goal adjustment measures are included simultaneously as predictors of well-being, accommodation remains as the strongest predictor (and partly goal reengagement as well), while goal disengagement shows opposing relationships with most measures of well-being.We discuss the lessons learnt from these findings and conclude by proposing future avenues to examine goal adjustment processes.